6 UMP subjects listed in QS World 2021 Ranking - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 4 March 2021 - Six Universiti Malaysia Pahang (UMP) subjects are listed in the QS World University Rankings by Subject 2021 announced today.